Rheological analysis of emulsion-filled gels based on high acyl gellan gum - Lorenzo, Gabriel (2013)
Emulsion-filled gels are widely used in cosmetic, food, and pharmaceutical industry. As rheological properties of these systems are strongly dependent on the properties of the gelled polymer network, rheological characteristics of gels containing high and low acyl gellan gum were analyzed. Under the processing conditions low acyl emulsions were unstable, thus in the present work the influence of oil and hydrocolloid concentrations on the viscoelastic behavior of emulsion-filled gels containing high acyl gellan gum was studied. Increasing gellan concentration (from 0.1 g/100 g to 0.5 g/100 g) produced stronger gels, while oil fraction (10 g/100 g-30 g/100 g) slightly affected the elastic behavior of the emulsions reinforcing the structure and the elastic characteristics of the gellan matrix. Sauter diameter (d 32) was measured for all emulsions and an average value of 12 μm was obtained. Rheological data (oscillatory and creep-recovery tests) were successfully modeled to interpret the structural characteristics of the gelled emulsions. The broadened Baumgaertel-Schausberger-Winter spectrum was used to represent the linear viscoelastic behavior of the continuous phase and the emulsified system, showing that the rheological behavior of the systems was controlled by the highly structured continuous phase rather than the contribution of filler lipid droplet in the emulsion. Relaxation spectra were validated using creep-recovery experiments. Regardless of hydrocolloid concentration, creep compliance of the gel emulsions decreased compared with their respective gels, showing that the inclusion of oil droplets produced a reinforcement of the structure and the gel strength of the matrix.